Pengaruh Curah Hujan dan Hari Hujan Terhadap Produktivitas Karet (Hevea brasiliensis Muell-Arg.) Berumur 10, 15 dan 20 Tahun di Kebun Aek Pamienke PT. Socfin Indonesia (SOCFINDO) - Wanda Andika Hasibuan; Irsal Irsal; Mariati (Talenta Publisher, 2018)
Water plays a major role in the process of rubber plant metabolism. An inappropriate amount of water has a negative impact on the achievement of rubber productivity. The aim of the research was to study the effect of rainfall and rainy day on the rubber productivity in 10, 15 and 20 years old. The research was conducted at Aek Pamienke Plantation PT. Socfin Indonesia (Socfindo), sub-district of Aek Natas, district of Labuhan Batu Utara, Province of North Sumatera from July to August 2017. This study used secondary data available in plantation administration, consisted of rubber productivity data in 2014, 2015 and 2016, whereas rainfall and rainy day monthly data in 2013, 2014 and 2015. The analytical method used is multiple linear regression analysis and correlation analysis. The feasibility regression model was tested with the classic assumption test consists of a normality test, heteroscedasticity test, multicollinearity test, and autocorrelations test by using SPSS v.22 statistical tool for windows. Classical assumption test results showed that the regression equation in rubber plants in 10, 15 and 20 years old have been qualified. The regression analysis showed that rainfall and rainy day variables partially and simultaneously influence unreal with alpha 5% (Sig > á 0,05) to increased rubber productivity in 10, 15 and 20 years old. The result of correlation analysis shows rainfall and rainy day variables have a strong relationship to the rubber productivity, with correlation values of rainfall and rainy days at 0,846.